Impact on academic performance of freshmen of the nursing course: relationship of stress levels, cortisol and salivary alpha-amylase in the teaching of human anatomy (Research, Society and Development, 2023)
The objective of the study was to evaluate the levels of salivary Cortisol and Alpha-amylase, relating them to the level of stress and academic performance of freshmen of the Nursing course, during the first practical evaluation of the Human Anatomy discipline. Saliva collection procedures were performed before and after the application of the practical assessment of Human Anatomy. Salivary Cortisol and alpha-amylase concentrations were evaluated by the ELISA method. The short version of the Stress Assessment Questionnaire in Nursing Students was used. Results: It was observed that the mean concentration of salivary cortisol was 0.421 ± 0.076 µg/dL and the final one was 0.572 ± 0.096 µg/dL, characterizing a significant increase of 35.8% (p